Asupan zat gizi makro, asupan zat besi, kadar haemoglobin dan risiko kurang energi kronis pada remaja putri - Imelda Telisa; Eliza Eliza (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
Teenagers are a group of ranges experiencing nutritional problems. Nutrition problems that often occur in adolescents are lack of nutrient intake which can trigger chronic energy deficiency (CED) and anemia as a result of iron deficiency. The purpose of the study was to analyze the relationship of macro nutrient intake, iron intake, hemoglobin levels to the risk of chronic energy deficiency. This study uses a case-control design, which was carried out on 72 Muhammadiyah 1 Palembang high school students consisting of 36 at risk of CED and 36 at no risk of CED. Data on macro-nutrient intake and Fe intake were obtained from the calculation of Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), Hemoglobin content data using the quick check method, and CED data through measurement of mid-upper arm circumference (MUAC). Data analysis using the Chi-square test at CI:95%. The results showed that there was a significant relationship between energy consumption and macronutrient intake (p=0,004), protein (p=0,004), fat (p=0,031), and iron intake (p=0,000) with the risk of young female CED. The absorption of macro and micronutrients influences. The conclusion, the risk of CED in adolescent girls. Suggestions, education and interventions need to be done related to the importance of paying attention to the nutritional status of adolescent girls. Remaja merupakan kelompok rentang mengalami masalah gizi. Masalah gizi yang sering terjadi pada remaja adalah kurangnya asupan zat gizi yang dapat memicu terjadinya kurang energi kronis (KEK) serta anemia sebagai akibat kekurangan zat besi. Tujuan penelitian untuk menganalisis hubungan asupan zat gizi makro, asupan zat besi, kadar haemoglobin terhadap risiko kurang energi kronis. Metode penelitian survei analitik dengan desain secara kasus kontrol. Penelitian dilakukan pada 72 siswi SMA Muhammadiyah 1 Palembang terdiri 36 berisiko KEK dan 36 tidak KEK. Data asupan zat gizi makro dan asupan Fe diperoleh dari perhitungan Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), data kadar Haemoglobin menggunakan metode quick cek, dan data KEK melalui pengukuran lingkar lengan atas (LiLA). Analisis data menggunakan uji Chi-square pada CI:95%. Hasil penelitian menunjukkan terdapat hubungan signifikan antara asupan zgizi makro energi (p=0,004), protein (p=0,004), lemak (p=0,031) dan asupan zat besi (p=0,000) dengan risiko KEK remaja putri. Kesimpulan, Risiko KEK pada remaja putri dipengaruhi oleh asupan zat gizi makro dan mikro. Saran, perlu dilakukan edukasi dan intervensi terkait pentingnya memperhatikan status gizi remaja putri.